An economic anthropology of computer-mediated non-monetary exchange in England - Harvey, John (2016)
This thesis presents two studies of computer-mediated non-monetary exchange. The Internet has improved the potential for previously unconnected people to organise into interest groups with the intent of meeting offline. This has resulted in a range of organisations emerging with the explicit aim of helping people to give and share resources. These organisations typically reject money and markets, insisting that social interaction should occur through generosity alone. The first study presents a netnography and depth interviews which reveal how technology is used to enact and influence the management of identity, partner selection, ritual normalisation, and negotiation of property rights. The findings have significant implications for the design and management of systems that encourage non-monetary forms of collaborative consumption. In the second study a longitudinal social network analysis reveals how the social structures involved in these systems have no obvious historical precedent. This has implications for the way in which the social sciences should conceptualise reciprocal economic arrangements. It also raises some sociological implications for the possibility of designing economic systems in the absence of money. Finally, a new approach is proposed which advocates diachronic analysis of property rights as a means to explain how markets and institutions that try to subvert markets exist alongside each other.